Impacto da doença de Parkinson sobre as características cinéticas e cinemáticas da tarefa de levantar e andar, em caidores e não caidores - Pelicioni, Paulo Henrique Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Background: Recent studies have shown that Parkinson's disease (PD) patients have some difficult to perform sequential tasks, as the sit-to-walk (STW) task. The difficult to perform this task may be attributed to the PD physical impairments, neurophysiologic and clinic impairments, the context that the task is performed and to the conservative pattern adopted for these patients. PD patients show some impairment in the motor circuitry, sensory processing and program of action. The STW task, like another sequential task requires continuous program end execution in healthy subjects. Therefore, we expect that PD patients perform this task with appropriate motor solutions, as for example, separate the STW in two distinct tasks to ensure the stability and demonstrate less risk of fall. Thus two hypotheses were developed: PD patients separate the STW in two distinct task and show some alterations in kinetic and kinematic parameters when compared with healthy matched-control; PD patients fallers show a more conservative behavior than non- fallers. Aim: To assess healthy elderlies, PD patients non-fallers and fallers motor behavior's in the STW in time constraints, in two different studies. Methods: 28 subjects participated in the study 1 and two different groups were established: GDP group, with 14 PD patients and GC group, with healthy matched-control. In the study 2, 26 subjects participated and two different groups were established: GNC group, with 13 PD patients non-fallers and GCA group, with 13 PD patients fallers (they have been considered fallers whether had fallen at least once in the last year). To perform the STW, the participants were seated in a chair armless and backless, barefoot on the two force plates. The height of chair was standardized in 0.42 m. After the subjects hear a mobile ring, they should rise from the chair and answer it. With their hands on their knees, the subjects rose from a chair immediately after the mobile...

Introdução: Recentes estudos têm demonstrado a dificuldade de pacientes com doença de Parkinson (DP) em realizar tarefas sequenciais, como o caso da tarefa de levantar e andar (LEA). A dificuldade em realizar tarefas dessa natureza pode ser atribuída às restrições físicas dessa população, aos aspectos neurofisiológicos e clínicos da DP, ao contexto em que a tarefa é realizada e também à escolha de um padrão precavido adotado por esses pacientes. Os pacientes com DP apresentam comprometimentos na circuitaria motora, no processamento sensorial e na programação da ação. A LEA, como outra tarefa motora sequencial, exige programação e execução contínua em indivíduos neurologicamente saudáveis, portanto, espera-se que pacientes com DP apresentem soluções adequadas ao seu contexto, como por exemplo, separar a tarefa em duas distintas a fim de garantir a estabilidade e apresentar menor risco de cair, principalmente quando realizada sob restrição temporal. Dessa forma duas hipóteses foram elaboradas para este estudo: pacientes com DP separam a tarefa de LEA com demanda temporal em duas distintas e apresentam modificações nos parâmetros cinéticos e cinemáticos durante a LEA com demanda temporal em comparação com seus pares neurologicamente saudáveis; pacientes com DP caidores apresentam um comportamento ainda mais precavido quando comparados a seus pares não caidores. Objetivo: Avaliar o comportamento motor de indivíduos idosos saudáveis e idosos com DP caidores e não caidores na tarefa de LEA com demanda temporal, em dois diferentes estudos. Método: No estudo 1, participaram 28 indivíduos, formando intencionalmente dois grupos: grupo GDP, com 14 pacientes com DP idiopática e o grupo GC com 14 indivíduos neurologicamente sadios (grupo controle). No estudo 2, participaram 26 indivíduos, formando intencionalmente dois grupos: grupo GNC, com 13 pacientes com DP idiopática não caidores e o grupo GCA, com 13...
Keywords: Physical education and training; Educação fisica; Parkinson, Doença de; Quedas (Acidentes); Locomoção humana; Mecanica humana; Capacidade motora